Comparison of muscle response in patients treated with rigid and flexible fixed functional appliances - Ruchi Saini; Puneet Batra; Nidhi Saini; Komal Punia; Tanjula Shair; Monis Raza (Wolters Kluwer Medknow Publications, 2024)
AIM: The present study was undertaken to evaluate and compare muscle activity after the treatment with rigid and flexible fixed functional appliance. MATERIAL AND METHOD: The study was conducted on 14 skeletal Class II malocclusion patients in the age group of 13-17 years, divided into two groups comprising 7 patients in each group. Group I was treated with a rigid fixed functional appliance (MPA IV), and Group II was treated with a flexible fixed functional appliance (Churro Jumper). Masseter and anterior temporalis muscle activities were recorded using needle electromyography (EMG) at postural rest, saliva swallowing, and clenching during five intervals (T0 to T4) during fixed functional appliance treatment. Unpaired t-test, Mann-Whitney U, and Wilcoxon sign rank test were applied for statistical analysis, and a P value of <.05 was considered statistically significant. RESULTS: Group I (MPA IV) showed a significant increase in EMG activity during postural rest position (P = 0.003, P = 0.001), swallowing (P = 0.013, P = 0.005), and clenching (P = 0.001, P = 0.002) in masseter and anterior temporalis muscle, respectively. Group II (Churro jumper) also showed a significant increase in EMG activity during postural rest position (P = 0.000, P = 0.000), swallowing (P = 0.001, P = 0.000), and clenching (P = 0.001, P = 0.000) in masseter and anterior temporalis muscle, respectively. CONCLUSION: Both rigid (MPA IV) and flexible (Churro Jumper) fixed functional appliances caused a significant increase in EMG activity of masseter and anterior temporalis muscle during postural rest position, swallowing, and clenching in 6 months of the observation period, but the flexible appliance (Churro Jumper) showed more significant increase.